2017
DOI: 10.1017/s0031182017000129
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnosis of Trichuris trichiura by using a bead-beating procedure on ethanol preserved stool samples prior to DNA isolation and the performance of multiplex real-time PCR for intestinal parasites

Abstract: SUMMARYFor the majority of intestinal parasites, real-time PCR-based diagnosis outperforms microscopy. However, the data for Trichuris trichiura have been less convincing and most comparative studies have been performed in populations with low prevalence. This study aims to improve detection of T. trichuria DNA in human stool by evaluating four sample preparation methods. Faecal samples (n = 60) were collected at Flores island, Indonesia and examined by microscopy. Aliquots were taken and a bead-beating proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 38 publications
6
91
2
Order By: Relevance
“…Interestingly, some authors also reported poorer DNA extraction after this step, depending of the extraction technique used and on the type of beads. For example, in the study of Kaisar et al [ 11 ], mechanical lysis diminished the number of positive samples for G. intestinalis and D. fragilis . In the same way, a multicentric study showed highly variable effects of the bead-beating step on the extraction of Cryptosporidium DNA, especially with the MagNA Lyser ® Green Beads which impacted it negatively [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some authors also reported poorer DNA extraction after this step, depending of the extraction technique used and on the type of beads. For example, in the study of Kaisar et al [ 11 ], mechanical lysis diminished the number of positive samples for G. intestinalis and D. fragilis . In the same way, a multicentric study showed highly variable effects of the bead-beating step on the extraction of Cryptosporidium DNA, especially with the MagNA Lyser ® Green Beads which impacted it negatively [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The POL method is similar to the technique of helminth DNA extraction described by Verweij (35) except the missing bead mill procedure, which was not available in our laboratories at the time of the study. The POL method was the only alternative method (with good results for protozoans) known, which could be used without a cell lysing instrument (9,18,22,36).…”
Section: Discussionmentioning
confidence: 99%
“…Two panels of multiplex real‐time PCR were used to detect and quantify soil transmitted helminths and intestinal protozoa. Panel 1 targets hookworm ( Ancylostoma duodenale, Necator americanus ), Ascaris lumbricoides , Trichuris trichuria and Strongyloides stercoralis , while panel 2 targets Entamoeba histolytica, Dientamoeba fragilis, Giardia lamblia and Cryptosporidium spp. .…”
Section: Methodsmentioning
confidence: 99%